Chapter 4 Theatre for Influence American Cultural and Philanthropic Missions in West Africa during the Early Cold War - Morison, Gideon Ime (Taylor & Francis, 2024)
Emerging from the superpowers' covert attempts to counter their political and ideological influence without direct military confrontations, the Cold War was also enacted in the cultural sphere of many third world countries, especially Africa, which became a 'site of encounter' for the staging of US-Soviet theatre of influence. In West Africa, Ghana and Nigeria were strategically adopted as epicentres of western cultural philanthropy through the funding of cultural institutions and networks of selected artists as well as the organisation, sponsorship and hosting of collaborative artistical events covering drama, music, dance, and the visual arts. This chapter shall discuss selected American-sponsored cultural events and programmes in these territories as a sub-set of the cultural Cold War dynamics directed towards the 'winning of hearts and minds' as well as the institutionalisation of liberal values within these emerging societies. Events such as the 1961 Lagos Festival (sponsored by the American Society of African Culture) and the 1967 Ghana Festival of Arts (sponsored by the United States Information Service) shall be examined to ascertain, from a comparative perspective, the underlying structures of collaboration, organisation and reception of these events within the Cold War context.